As for an issue of the origins and the resettlement of Bulgariansʼ Tuqan ethnographic group in Ukraine - Alexander Ganchev (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2019)
The Bulgarians' resettlement to Bessarabia lasted during almost five centuries. It was likely to start at once after the Ottoman's conquest of Bulgaria in the end of XIV century. Since then intensity of migration obviously was different and at the same time it was isolated occurrence and wasn't a reason for places of the Bulgarians' concentration to appear.